The Utopia of Mass Media: Towards Public-generated Media - Pajnik, Mojca (Sociologija. Mintis ir veiksmas, 2015)
The paper deals with contemporary mass media dependence on politics and capital and attempts to discern what, if anything, is still public about mass media in general, and public broadcasting in particular. A consideration of the public as a phenomenon of individual aspirations is central to this discussion, seeing as it will help shed light on public broadcasting’s (in)ability to encompass the public’s activity, particularly when addressing the public in its transnational appearances. The paper makes use of public broadcasting in Slovenia as a model through which it examines public broadcasting as a framework for the economic and political interests of the nation-state. The paper proceeds to thematize lack of potential of public broadcasting to address the dispersed public that is emerging transnationally, outside of fixed ideas of identity and national affiliations. The argument is presented as for why contemporary discussions of the potentials of the public in its relation to the media should consider the practices of the public not only in the sphere of mass media, but also beyond and, to a certain extent, in contrast to mass media – through examples of attempts to reactivate the public in the potentials of “public-generated media”.